Natural compound chaetocin induced DNA damage and apoptosis through reactive oxygen species‐dependent pathways in A549 lung cancer cells and in vitro evaluations - Qi Zhang; Feng Ruan; Maonan Yang; Qinghui Wen (IET Nanobiotechnology)
Abstract There is an urgent need for potential pharmaceutics for lung cancer treatment due to the increased number of lung cancer deaths and the resistance of cancer cells to present therapeutics. The present work aims to discover the anticancer potential of the natural compound chaetocin as a therapeutic for lung cancer treatment. Results showed the significance of chaetocin‐induced cell growth inhibition by the expression of G2/M phase arrest and reactive oxygen species (ROS) dependent apoptosis in A549 lung cancer cells. Results concluded that chaetocin could produce ROS and nuclear damage against A549 lung cancer cells. Interestingly, chaetocin exhibits a significant level of CD47 that down‐regulates the expression of CD47 at mRNA levels. PBMC biocompatibility study revealed that chaetocin is non‐toxic to normal cells. Overall, experimental results suggested that chaetocin induces A549 cell apoptosis, by causing ROS and nuclear damage activation pathways. In the future, chaetocin might be an effective bio‐safe anticancer agent for lung cancer treatments.